SURVEY ABOUT THE ROLE OF AGE, HYPERTENSION, AND DIABETES ON THE SEVERITY OF COVID-19 - Trần , Đăng Ninh; Lê , Văn Tám; Lê , Phước Phương; Đặng , Văn Khanh; Đặng , Thị Trà My (Journal of 175 Practical Medicine and Pharmacy, 2023)
Background: The global outbreak of highly contagious coronavirus 2019 has led medical system of nations, psychological, and socio – economic conditions to a challenging situation that they never thought before. Covid -19 portrays probably one of greatest threats in this century that the countries have to tackle. Therefore, scientists are trying to understand the pathogenesis, clinical implications, and develop novel preventive strategies. Objective: to evaluate the impact of age, comorbidities on the severity of Covid – 19. Methods: retrospective cross – sectional study. Result: presence of at least one comorbidity hypertension, diabetes individually increased the severity of Covid - 19 cases significantly (OR: 12, p = 0,000, (95%CI: 4,2 – 35,5)). Cases at the age of ≥ 50 years (OR = 4,9, p = 0,002 (95%CI: 1,78 – 13,46) were severely affected by SARS – CoV -2. Conclusions: older patients (age ≥ 50 years) are at higher risk of developing severity, whereas comorbidities could significantly affect the severity of Covid -19